Robust Sampled-Data Consensus-Based Cooperative Control of Multi-UAVs - Di Ferdinando, M.; Pepe, P.; Di Gennaro, S. (Mediterranean Conference on Control & Automation, 2021)
In this paper, the sampled-data formation control problem of multi unmanned aerial vehicles (UAVs), affected by actuation disturbances and observation errors, over strongly directed networks is studied. In particular, a robust consensus based sampled-data protocol enabling a connected and leaderless swarm of UAVs to reach a desired formation in altitude and position is proposed. The provided sampled-data control algorithm relies on the architecture of leaderless consensus, in which each UAV communicates with the adjacent UAVs only and, furthermore, on the input-to-state stability redesign methodology which is used in order to attenuate the effects of any bounded actuation disturbance and of any sufficiently small observation error. A sampled-data control strategy for the collision avoidance of adjacent UAVs is also included. The theory of the stabilization in the sample-and-hold sense is used as a tool in order to prove that the sampled-data leaderless consensus of the multi-UAVs swarm is ensured, regardless of the above disturbances and errors. Actuator disturbances are assumed to be bounded with arbitrarily large a-priori known bound. Simulations show the good performances of the proposed robust sampled-data control algorithm.